Die Relevanz von Sprechflüssigkeit in der interkulturellen Lehr-/Lernkommunikation am Beispiel studentischer Referate – ausgewählte empirisch basierte Erkenntnisse - Grzeszczakowska-Pawlikowska, Beata (2023)
This paper assumes the high communicative relevance of fluency in intercultural university communication, where lecturing in the form of seminar presentations constitutes one of the most important key academic skills. An essential prerequisite for the transfer of knowledge from students to fellow students is not only appropriate subject knowledge, but also includes a range of rhetorical skills, which are indispensable even during the preparation of a presentation. Finally, it comes down to the ability to (largely) speak freely, which is often quite a challenge for inexperienced speakers. This is especially true for foreign-language students, as possible linguistic and/or phonetic inadequacies of non-native speakers can be an additional hurdle in the smooth running of speech thought processes and thus in free fluent speech. Speaking with little or insufficient fluency can, under certain circumstances, trigger specific unintended communication effects, such as negative speaker attributions, impaired intelligibility and even loss of content. This problem is discussed in detail in this paper.
Keywords: speech fluency; impact of disfluency on recipients; intercultural academic communication